Brewing potential of strains of the boreal wild yeast Mrakia gelida - Linnakoski, Riikka; Jyske, Tuula; Eerikäinen, Ronja; Veteli, Pyry; Cortina-Escribano, Marta; Magalhães, Frederico; Järvenpää, Eila; Heikkilä, Lotta; Hutzler, Mathias; Gibson, Brian (Frontiers in Microbiology, 2023)
Demand for low- or non-alcoholic beers has been growing in recent years. Thus, research is increasingly focusing on non-Saccharomyces species that typically are only able to consume the simple sugars in wort, and therefore have a limited production of alcohol. In this project, new species and strains of non-conventional yeasts were sampled and identified from Finnish forest environments. From this wild yeast collection, a number of Mrakia gelida strains were selected for small-scale fermentation tests and compared with a reference strain, the low-alcohol brewing yeast Saccharomycodes ludwigii. All the M. gelida strains were able to produce beer with an average of 0.7% alcohol, similar to the control strain. One M. gelida strain showing the most promising combination of good fermentation profile and production of desirable flavour active compounds was selected for pilot-scale (40 L) fermentation. The beers produced were matured, filtered, carbonated, and bottled. The bottled beers were then directed for in-house evaluation, and further analysed for sensory profiles. The beers produced contained 0.6% ABV. According to the sensory analysis, the beers were comparable to those produced by S. ludwigii, and contained detectable fruit notes (banana, plum). No distinct off-flavours were noted. A comprehensive analysis of M. gelida’s resistance to temperature extremes, disinfectant, common preservatives, and antifungal agents would suggest that the strains pose little risk to either process hygiene or occupational safety.